JJCO Best Reviewer Award (Japanese Journal of Clinical Oncology, 2020)
AIM: This retrospective comparative study aimed to assess the feasibility and benefits of newly developed pneumovaginoscopy-assisted radical hysterectomy (PVRH) combined with systemic chemotherapy (neoadjuvant and adjuvant) compared to primary concurrent chemoradiotherapy in the treatment of stage IIB-IIIA locally advanced cervical cancer. METHODS: Between June 2014 and December 2023, 117 patients with stage IIB-IIIA cervical cancer were treated. Fifty-nine patients were treated with PVRH combined with systemic chemotherapy [45 patients with neoadjuvant chemotherapy (NAC) and adjuvant chemotherapy, 14 patients with adjuvant chemotherapy only)] or with primary concurrent chemoradiotherapy (n = 58). RESULTS: The neoadjuvant chemotherapy, pneumovaginoscopy-assisted radical hysterectomy, and adjuvant chemotherapy (NPA) completion rates were all 100%. The adjuvant radiotherapy avoidance rate was 94.8%. All patients resumed self-urination within 3 months of surgery. The achievement rates of R0 resection were 100% for vagina and 97.8% (1/45 of NAC cases) for parametrium. The adverse events associated with NPA were less severe than those associated with primary concurrent chemoradiotherapy. The patients with complete or partial response by NAC had a prognosis comparable to primary concurrent chemoradiotherapy; however, the patients with stable disease by NAC had a significantly poorer prognosis than primary concurrent chemoradiotherapy. In squamous cell carcinoma, the rate of distant metastasis was numerically lower with NPA group compared to the concurrent chemoradiotherapy group; however, this trend was not observed in the subgroup that showed a poor response to preoperative chemotherapy. CONCLUSIONS: Endoscopy-assisted precise RH with perioperative chemotherapy is a feasible multidisciplinary strategy for stage IIB-IIIA cervical cancer, demonstrating high surgical precision and functional preservation. While these results may suggest potential benefits of this treatment, their interpretation requires caution, and patient selection based on the response to preoperative therapy is considered important.